MiRroring the Multiple Potentials of MicroRNAs in Acute Myocardial Infarction - Paiva, Solenne; Agbulut, Onnik (Frontiers in Cardiovascular Medicine, 2017)
At present, cardiovascular diseases are depicted to be the leading cause of death worldwide according to the World Health Organization. In the future, projections predict that ischemic heart disease will persist in the top main causes of illness. Within this alarming context, some tiny master regulators of gene expression programs, namely microRNAs carry three promising potentials. In fact, miRNAs can prove to be useful in terms of biomarkers allowing heart injury detection, but also in terms of therapeutics to overcome limitations of past strategies and treat the lesions. In a more creative approach, they can even be used in the area of human engineered cardiac tissues as maturation tools for cardiomyocytes derived from pluripotent stem cell. Very promising not only for patient-specific cell-based therapies but also to develop biomimetic microsystems for disease modelling and drug screening, these cells greatly contribute to personalized medicine. To get into the heart of the matter, the focus of this review lies primarily on microRNAs as acute myocardial infarction biomarkers. Only large cohort studies comprising over one hundred individuals to reach a potent statistical value were considered. Certain miRNAs appeared to possibly complement protein-based biomarkers and classical risk factors. Some were even described to bear potential in the discrimination of similar symptomatic pathologies. However, differences between pre-analytical and analytical approaches substantially influenced miRNA data. Further supported by meta-analysis studies, this problematic had to be addressed. A detailed critical analysis of each step to define miRNAs biomarker potential is provided to inspire a future improved universal strategy. Interestingly, a recurrent set of cardiomyocyte-enriched miRNAs was found, namely miR-1; miR-133; miR-208a/b and miR-499a. Each member of this myomiRs group displayed promising roles either individually or in combination as acute myocardial infarction diagnostic or prognostic biomarkers. Furthermore, a precise combo was shown to be powerful enough to transdifferentiate human fibroblasts into cardiomyocytes opening doors in the therapeutics. Following these discoveries, they also emerged as optional tools to transfect in order to mature cardiomyocytes derived from pluripotent stem cells. Ultimately, the multiple potentials carried by the myomiRs miR-1; miR-133; miR-208a/b and miR-499a still remain to be fully unveiled.